Optimization of Project Duration in Uncertain Condition through Fuzzy Logic Approach - Pal, Animesh; Pal, Anindita (International Journal of Scientific Research in Civil Engineering, 2018)
Construction industry is very complex system and needs to adapt most systematic as well as rational approach to optimize project duration to complete undertaken projects within stipulated time, budget and required quality. In process of optimization, a large number of interactive variables of the project creates problem, so need to determined there impact to reach any decision. Linear programming model help to optimize decision making in rigid environment, but in real working environment where goals, constrains, consequence of action are not known precisely, uncertainty play major factors  toward project success and performance, need certain degree of flexibility to be incorporated in decision making  model to optimize project duration. This paper demonstrates with fuzzy linear programming model to incorporate flexibility in project scheduling with a case study.
Keywords: Fuzzy set; Linear Programming model; Fuzzy linear Programming; Optimization in Uncertain Environment